A 1, 2‐trans‐Selective Glycosyl Donor Bearing Cyclic Protection at the C‐2 and C‐3 Hydroxy Groups. Issue 32 (28th August 2017) - Yagami, Nahoko; Tamai, Hideki; Udagawa, Taro; Ueki, Akiharu; Konishi, Miku; Imamura, Akihiro; Ishida, Hideharu; Kiso, Makoto; Ando, Hiromune
Abstract : A new 1, 2‐ trans ‐selective glycosylation reaction is described. Glucosyl donors protected cyclically at the C‐2 and C‐3 hydroxy groups as six‐ (butane diacetal), seven‐ (tetraisopropyldisiloxanylidene), or eight‐ (2, 3‐ o ‐xylylene) membered fused rings were synthesized in a straightforward manner. The glycosylation reactions of the glucosyl donors with various acceptors mainly generated β‐glycosides under conventional reaction conditions. The results show that the o ‐xylylene group is a suitable 1, 2‐ trans ‐directing group from the points of view of stereoselectivity and chemical stability. A conformational study of the oxocarbenium ion of an o ‐xylylene‐protected glucose derivative by NMR spectroscopy and computational simulation was carried out. The results imply that the oxocarbenium ion mainly adopts a 4 H 3 conformation owing to the rigid trans ‐fused ring at C‐2 and C‐3, while a noncyclically protected derivative might fluctuate between conformations. These results suggest that an eclipsing interaction between the pseudoequatorial xyloxy group at C‐2 and the incoming nucleophile hampers 1, 2‐ cis attack. Abstract : A new 1, 2‐ trans ‐selective glycosylation reaction is described. Glucosyl donors protected cyclically at the C‐2 and C‐3 hydroxy groups mainly generated β‐glycosides under conventional glycosylation conditions. The results show that the o ‐xylylene group can be used as a 1, 2‐ trans ‐directing group.